Status of intrinsic motivation of the white-collar employees: Is everyone equally motivated? - Bhattarai, Ganesh; Shah, Kapil (NCC Journal, 2021)
As white-collar employees are more concerned and value the job's intrinsic aspects, this study concentrated on the intrinsic motivation of white-collar employees. This study was dedicated to measuring the general status of the intrinsic motivation of different groups of gender, age, education, experience, and designation. Moreover, this study was dedicated to measuring whether there are differences in intrinsic motivation between and among various groups of employees in terms of their demography (i.e., gender, age, education, experience, and designation). Data were collected among the white-collar employees working in the Nepalese insurance industry. Cross-sectional and perceptual data was analyzed using SPSS. Three hundred fifty-eight responses were analyzed quantitatively. This study measured that white-collar employees working in the insurance industry were intrinsically motivated. Male employees were more intrinsically motivated than female coworkers. Old-aged employees' intrinsic motivation was higher than younger employees. Likewise, this study revealed that employees' intrinsic motivation within the education, experience, and designation groups was similar. Different practical and theoretical implications and directions for future research are suggested.